A centennial bibliography of Huntington's Chorea 1872-1972 - Bruyn, G. W.; Baro, F.; Myrianthopoulos, Ntinos C. (Ntinos Cleovoulou) (The Hague : Nijhoff, 1974)
Over 2000 references to comprehensive world literature. Only original works included, i.e., not abstracts or reviews. Chronological arrangement of entries. Besides bibliographical information, entries also include subject category code letters. Most titles are given in the original languages. Category index, Geography index, Entry indes, Author index.
Includes indexes.
Keywords: Huntington Disease -- Bibliography